Rasionalitas Pemilihan Kerja Sebagai Guru - Ulfi, Brilliansyah; Handoyo, Pambudi (Paradigma, 2025)
This study aims to understand and analyze the rationality of individual actions in choosing a profession as a teacher at MTs Muhammadiyah 1 Taman. The focus of the study is directed at revealing subjective motivation, social driving factors, and classification of actions based on Max Weber's social action theory framework. This study uses a qualitative approach with an interpretative understanding perspective and data collection techniques through observation, in-depth interviews, and documentation. The research subjects were selected using purposive sampling techniques, with criteria of work experience, social status, and educational background. The results of the study indicate that the decision to choose a teaching profession is not only based on economic rationality, but is more influenced by value rationality, affection, tradition, and short-term practical considerations. Instrumental rationality is reflected in subjects who make the teaching profession a stepping stone to a formal career. Value rationality is seen in subjects who are motivated by religious values, obedience to parents, and idealism of devotion. Traditional actions appear in alumni teachers who choose to teach at the same school because of historical ties, while affective actions appear in subjects who maintain their profession because of emotional comfort and a conducive working atmosphere. The conclusion of this study confirms that the choice of work as a teacher at MTs Muhammadiyah 1 Taman is the result of a combination of subjective and objective factors that cannot be explained by an economic approach alone. The context of Islamic values, the structure of Muhammadiyah's Charity, and local social relations greatly influence the construction of the meaning of the work of these teachers